The impact of heterogenous consumer preferences on welfare outcomes of government interventions - Hawthorne, Ryan (School of Economics, 2019)
Heterogeneity in the demand for telecommunications services in South Africa is investigated here in three contributions. The results of this research show that government interventions in the telecommunications sector over the last decade have had significantly different effects on different groups of consumers, and in particular that the rich have benefited more than the poor. Heterogeneous consumer preferences are especially interesting to study in highly unequal developing countries like South Africa, where the discriminatory policies implemented during apartheid have resulted in a deeply divided society. For example, the results of the first contribution show how the regulation of mobile termination rates (MTRs, which were reduced by 90% between 2009 and 2017) accounted for around 60% of the reduction in quality adjusted postpaid prices in South Africa, used mainly by high-income consumers. However, MTR reductions accounted for only 30% of the reduction in prepaid prices, typically used by poor consumers. Quality-adjusted prices and the effects of lower MTRs have previously been studied in developed countries where prepaid does not matter as much, and these studies have typically used average, aggregate price data or data on an individual operator. In this contribution, the effects of lower MTRs are evaluated using a unique dataset on 2,773 operator-level mobile tariffs over the period between 2009 and 2017 in a developing country, South Africa. The variation in prices at the operator level is further exploited to show that on-net and off-net prices converged as a result of lower termination rates. This reduces the ability of firms with market power to use high MTRs to generate tariff-mediated network effects to exclude rivals. In the second contribution, the effects of consumer heterogeneity are further explored by developing a structural model of demand and supply in a discrete-choice framework. We test for the distributional effects of regulation and entry in the mobile telecommunications sector in a highly unequal country, South Africa. Using six waves of a consumer survey of over 134,000 individuals between 2009-2014, we estimate a discrete-choice model allowing for individual specific price-responsiveness and preferences for network operators. Next, we use a demand and supply equilibrium framework to simulate prices and the distribution of welfare without entry and mobile termination rate regulation. We find that regulation benefits consumers significantly more than entry does, and that high-income consumers and city-dwellers benefit more in terms of increased consumer surplus. In the third contribution, we exploit the discriminatory roll-out of fixed-lines during apartheid to Whites-only areas to study fixed and mobile substitution, using the same survey data. In our discrete-choice model, individuals choose fixed or mobile voice and data services in a framework that allows them to be substitutes or complements. We find that voice services are complements on average but data services are substitutes. However, many consumers see data services as complements. Our results show that having a computer and access to an internet connection at work or school are more important than reducing mobile data prices by 10% in driving broadband penetration.